The Strategies and Orientation of Translating Idiomatic Expressions in Twain’s The Adventures of Huckleberry Finn Novel - Lutfia Hanim; Tofan Dwi Hardjanto (Vivid: Journal of Language and Literature, 2021)
In translating idiomatic expressions, strategies are applied in order to make the result equivalent in the target language. This research proposes to explore the strategies used in translating idiomatic expressions and translation orientation. Translating idiomatic expressions might cause difficulties for translator and the result tend to be based on the source or target language. Therefore, we proposed to investigate the translation strategies of the novel “The Adventures of The Huckleberry Finn”. It aims at deciding the most frequent strategies used in the translating idiomatic expressions and translation orientation. This research is descriptive qualitative study using content analysis applying purposive sampling technique since not the whole novel is investigated. This finding shows that there are 53 idiomatic expressions translated using strategies proposed by Mona Baker (2018). This research also found that there are four strategies are used by the translator, such as (1) using an idiom of similar meaning and form; (2) translation by omission of entire idiom; (3) translation by paraphrase; and (4) translation by omission of a play on idiom. The most frequent strategy is translation by paraphrase with 51.8% occurence. Furthermore, domestication is dominating the orientation of the translation.